Kangerlussuaq, Greenland, warming and exclosure experiment shrub abundance data 2003-2017 ... - Post, Eric; Pedersen, Christian (Arctic Data Center, 2021)
These data include annual peak abundances of two deciduous shrubs, dwarf birch (Betula nana) and gray willow (Salix glauca), sampled non-destructively from 2003-2017 near Kangerlussuaq, Greenland, as part of an ongoing experiment. The experiment involves exclusion of large herbivores (caribou and muskoxen) and passive warming according to the International Tundra Experiment protocol, and was motivated by an interest in investigating interactive and singular influences of herbivory and warming on plant abundance and community composition. Data include annual aboveground total abundance of each species on experimental plots under four treatment/control combinations: exclosed ambient, exclosed warmed, grazed ambient, and grazed warmed. ...